Pemilihan Canvaser Terbaik Menggunakan Metode Analitical Network Process Di Indosat Ooredoo - Ina Syafitri; Harly Okprana; Ilham Syahputra Saragih (STMIK Budi Darma, 2021)
Sales sales are one of the professions that spearhead the company in introducing its products to be known for and benefit to the public, as well as lead the prospects for a company meeting its established sales goals. In order for continuous sales conditions to be motivated to meet the company's established target of sales, appreciation should be given in reward for gains. In order for the reward to be conducted with objective and targeted objectives, it is necessary for a decision support system that helps indosat ooredo city of stabilizers to determine which sales are the best. In view of the fact that sales restructurization will not be done properly, it will create a stigma on both the management and the spirit and motivation of sales and retail sales. The research aims to identify the most influential criteria for best sales suppressors. The weight and priority of the criteria tested by the analytical network process (anp) are also intended to generate intermutual relationships between those criteria beyond the criteria for prioritizing alternatives.